PENGARUH MODAL USAHA DAN TINGKAT PENDIDIKAN TERHADAP PENINGKATAN PENDAPATAN UMKM DI KECAMATAN ALOK TIMUR KABUPATEN SIKKA - Cismawati, Maria Mensiana; Herdi, Henrikus; Yuneti, Katharina (Universitas Nusa Nipa Maumere, 2025)
This research aimed to examine and analyze how business capital and education level affect the income level of MSMEs in East Alok Sub-district, Sikka Regency. The data collection techniques used in this study were observation, questionnaire, interview, and documentation methods. This research employed a quantitative method. The results of the analysis showed that (1) business capital has a positive effect on increasing the income of MSMEs in East Alok Sub-district, Sikka Regency, (2) education level has a positive effect on increasing the income of MSMEs in East Alok Sub-district, Sikka Regency, and (3) business capital and education level together have a positive effect on increasing the income of MSMEs.